2010
DOI: 10.1159/000316171
|View full text |Cite
|
Sign up to set email alerts
|

Nailing down the Genetic and Immunological Basis for Psoriatic Disease

Abstract: Psoriatic disease encompassing skin, joint and nail involvement is largely viewed as autoimmune – a finding supported by data from animal models, the human leucocyte antigen (HLA)-Cw6 disease association in man, T-lymphocyte infiltration in lesional skin and the favourable skin response to T-cell-directed therapies. However, this immunopathogenetic model only applies to the skin, as recent studies failed to demonstrate a HLA-Cw6 association with the nails or joints. Furthermore, the nails and joints are intima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 70 publications
(45 reference statements)
2
35
0
5
Order By: Relevance
“…McGonagle et al [11 ]reported that T-cell-mediated immunity is predominant in skin lesions and innate immune responses may have a key role, especially in nail and joint involvement of the psoriatic patients. In this respect, the anti-inflammatory MTX seems to be more effective than the T-cell-inhibiting cyclosporine in nail psoriasis [11]. …”
Section: Discussionmentioning
confidence: 99%
“…McGonagle et al [11 ]reported that T-cell-mediated immunity is predominant in skin lesions and innate immune responses may have a key role, especially in nail and joint involvement of the psoriatic patients. In this respect, the anti-inflammatory MTX seems to be more effective than the T-cell-inhibiting cyclosporine in nail psoriasis [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent imaging, histological and genetic studies have suggested a new link between joint and nail disease. Frequent microdamage and tissue repair at normal enthesis attachment sites in healthy joints has resulted in a proposed new model of psoriatic arthritis pathogenesis embracing the concept of autoinflammation, whereby tissue-specific factors, including microtrauma, lead to regional innate immune activation and persistent inflammation, as an alternative to primary immunopathology driven by T and B cell abnormalities [8,9]. If such is the case, early treatment of severe nail disease might offer additional benefit to the patient by diminishing joint inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Nail involvement in psoriasis may have two basic patterns, one related to epidermal changes such as subungual hyperkeratosis and a second pattern that might be associated with the entheses that anchor the nail matrix and nail plate region [15]. In the latter case, we hypothesised that the involvement of the nail matrix by the inflammatory process might contribute to lesions such as pitting in a linear pattern consistent with the ‘finger-like’ attachment of the ligamentous structures linking the nail to the extensor tendon and distal interphalangeal joint capsule [16].…”
Section: Introductionmentioning
confidence: 99%